Associação entre exposição a adversidades na infância e tabagismo na vida adulta - Faria, Ana Paula Araújo (2015)
The association between adverse childhood experiences and smoking has been documented in scientific literature. However, few studies evaluating systematically role of exposure to these childhood experiences in the occurrence of this outcome in adult life. The aim of this study is evaluate the influence of exposure to a wide variety of adverse experiences occurring in childhood in the occurrence of smoking and early smoking through two studies: a systematic review and analysis of epidemiological study of mental disorders São Paulo Megacity. The systematic review was a search for articles using the following search terms: adverse childhood experience, childhood maltreatment, childhood abuse, child abuse and nicotine dependence, smoke, tobacco addiction, tobacco smoking that lead to identification of selected articles in 2632 of which 30 met the criteria for inclusion in the study. The results were: the 30 articles evaluated in the systematic review only three did not find association between the variables. The second study was conducted with a random sample of the general population (18 years or older) in the metropolitan São Paulo in which they were performed association analyzes (odds ratio - OR). The analyzes were performed using the statistical program Data Analysis and Statistical Software Release 12.0 (STATA 12.0) as a result it was demonstrated that there was a statistically significant association between exposure to adversities in childhood and smoking for most adversity, except sexual abuse, parental loss and economic adversity. All adversities, except sexual abuse and economic adversity, were associated with a higher chance of becoming nicotine dependent earlier, even after adjusting for gender, birth-cohort and highest parents’ education.